Exposure to pesticides in Chile and its relationship with carcinogenic potential: a review - Muñoz-Quezada, María Teresa; Iglesias, Verónica; Zúñiga-Venegas, Liliana; Pancetti, Floria; Foerster, Claudia; Landeros, Natalia; Lucero, Boris; Schwantes, Daniel; Cortés, Sandra (Frontiers in Public Health, 2025)
BackgroundThe widespread application of pesticides in agriculture and the consequent heightened human exposure to these potentially harmful substances present considerable environmental and health risks. The potential link to cancer is particularly concerning, underscoring the urgent need for more sustainable and health-conscious agricultural practices. Pesticides are pervasive global contaminants, with exposure occurring through various routes. Improper use is associated with genotoxicity, neurobehavioral problems, thyroid dysfunction, reproductive issues, and cancer, among other deleterious damages. While pesticide exposure is evident in Chile, a direct link to cancer remains uncertain.ObjectiveTo examine the scientific evidence on pesticides exposure in the environment and human populations, and its relationship with cancer in Chilean territory.MethodsThe search for original articles was performed in international peer-reviewed scientific databases, including Scopus, Web of Science (WoS), and PubMed Advanced Search Builder. Following the PRISMA extension for review guidelines, the search included studies on environmental pesticide exposure, human biomarker assessments, experimental investigations, and the potential pesticide-cancer associations in Chile. Foreign studies, systematic reviews, and meta-analyses were excluded.ResultsAmong the 83 qualifying studies conducted between 1996 and 2024, elevated pesticide exposure risks were documented, with 71% indicating high concentrations that may pose health risk. Additionally, 20% of studies reported significant chlorinated compounds, including organochlorines (OCs) and polychlorinated biphenyls (PCBs), while 79.5% identified carcinogenic to humans classified by the International Agency for Research on Cancer. The review emphasizes the urgent need to update pesticide-related regulations in Chile, including implementing bans or restrictions on carcinogenic pesticides and establishing stricter standards for allowable pesticide residue levels in food.ConclusionLong-term epidemiological studies are essential to establishing concrete links between pesticide exposure and specific types of cancer. Additionally, investigating epigenetic markers associated with pesticide exposure, especially in occupational settings, is critical. Furthermore, allocating resources and prioritizing further research is fundamental, particularly in regions with substantial agricultural exposure.